The impact of COVID-19 on aquaculture in China and recommended strategies for mitigating the impact - Yuan Yuan; Weimin Miao; Xinhua Yuan; Yunyun Dai; Yongming Yuan; Yunchong Gong (Wiley Online Library, 2025)
We carried out a preliminary investigation to study the impact of COVID-19 on aquaculture in China and identify the strategies and measures that have been taken by the Chinese Government. The investigation involved questionnaire surveys designed for all stakeholders along the industrial chain, including grow-out farmers, seed producers, fish processors, fish traders, and feed companies engaged in the catfish sector in Hubei Province and the tilapia sector in Guangdong Province during the strict period of control and after these control measures were lifted. We also attempted to summarize the government interventions and measures taken by different stakeholders along the value chain to minimize the damage caused by COVID-19 and support the recovery of different sectors in the aquaculture industry. We found that due to delayed harvesting, fish stocks were held-up in ponds and normal farming was interrupted. Farmers and traders were more severely impacted by the pandemic than other sectors. Furthermore, a series of strategies and measures are recommended to cope with the pandemic and other similar risks in the future. We expect that this study will provide good evidence for international societies to support the aquaculture industry in minimizing the impact of the pandemic and the rapid recovery of the industry in the post-pandemic period.